Implementasi Strategi Pendidikan Muktikultural Berbasis Kearifan Lokal di Sekolah Dasar - Maulida, Rifka; Laila Hidayati, Fatma; Mubin, Nurul (Tashdiq: Jurnal Kajian Agama dan Dakwah, 2024)
This research aims to analyze the implementation of multicultural education strategies based on local wisdom in elementary schools. This strategy aims to create a learning environment that is inclusive, tolerant and based on local cultural values. Using a qualitative approach, this research was conducted at several elementary schools in Central Java and East Nusa Tenggara. The research results show that local wisdom values ​​are integrated in the curriculum, interactive learning activities, culture-based extracurriculars, teacher training, and community involvement. This implementation has had a positive impact, despite challenges such as limited resources and ongoing support.